The Relationship Between Financial Managers’ Leadership Style and the Quality of Financial Reporting in Organizations - Kalateh, Sima (Business, Marketing, and Finance Open, 2026)
This study was conducted to examine the relationship between financial managers’ leadership style and the quality of financial reporting in organizations. This research is applied in terms of purpose and descriptive-correlational in terms of implementation method. The statistical population consisted of all financial managers, accountants, and auditors employed in organizations. A sample of 212 participants was selected using stratified random sampling. Data were collected using the standardized Multifactor Leadership Questionnaire (MLQ) and the Financial Reporting Quality Questionnaire developed by Kawasi (2021). Data analysis was performed at both descriptive and inferential levels using Structural Equation Modeling based on the Partial Least Squares approach (PLS-SEM) through SmartPLS version 3 software. The results indicated a positive and strong relationship between transformational leadership style and financial reporting quality (β = 0.552, t-value = 8.899), a positive and moderate relationship between transactional leadership style and financial reporting quality (β = 0.358, t-value = 3.429), and a negative and weak relationship between laissez-faire leadership style and financial reporting quality (β = -0.259, t-value = 2.675). All relationships were statistically significant at the 95% confidence level. Financial managers who adopt a transformational leadership style, characterized by inspirational motivation, intellectual stimulation, and individualized consideration, can significantly enhance the quality of financial reporting. In contrast, the laissez-faire leadership style exerts an adverse effect on reporting quality. Therefore, emphasizing transformational leadership competencies in the selection and development of financial managers is recommended as a key behavioral factor for improving the transparency and reliability of financial information.